Prognostic and Predictive Significance of Primary Tumor Localization and HER2 Expression in the Treatment of Patients with KRAS Wild-Type Metastatic Colorectal Cancer: Single-Centre Experience from Serbia - Radić, Jelena; Nikolić, Ivan; Kolarov-Bjelobrk, Ivana; Vasiljević, Tijana; Djurić, Aleksandar; Vidović, Vladimir; Kožik, Bojana (Journal of personalized medicine, 2024)
The treatment of patients with metastatic colorectal cancer (mCRC) is complex and is impacted by the location of the primary tumor (LPT). Our study aims to emphasize the importance of LPT as a prognostic and predictive marker as well as to examine the significance of HER2 overexpression in patients with mCRC, particularly in relation to the response to Epidermal Growth Factor Receptor Antibody treatment (anti-EGFR therapy). In this study, 181 patients with Kirsten RAS (KRAS) wild-type mCRC who received anti-EGFR therapy were included. Among them, 101 had left colon cancer (LCC) and 80 had right colon cancer (RCC). Results demonstrated that patients with KRAS wild-type LCC had better median overall survival (OS) (43 vs. 33 months, p = 0.005) and progression-free survival (PFS) (6 vs. 3 months, p < 0.001) compared to those with RCC. Multivariate analysis identified mucinous adenocarcinoma (p < 0.001), RCC location (p = 0.022), perineural invasion (p = 0.034), and tumors at the resection margin (p = 0.001) as independent predictors of OS, while mucinous adenocarcinoma (p = 0.001) and RCC location (p = 0.004) independently correlated with significantly shorter PFS. In addition, human epidermal growth factor receptor 2 (HER2) positive expression was significantly associated with worse PFS compared to HER2 negative results (p < 0.001). In conclusion, LPT is an important marker for predicting outcomes in the treatment of wild-type mCRC using anti-EGFR therapy, since patients with RCC have a statistically significantly shorter PFS and OS. Further investigation is needed to understand the role of HER2 overexpression in wild-type mCRC, as these patients also exhibit shorter survival.